Odpowiedzi

2009-10-14T17:52:33+02:00
Y-cena drugiego przedmiotu
x-cena pierwszego przedmiotu

x+y=2050. (x=2050-y)
33,2%*x+25%*y=30%*(x+y)
x+y=2050 33,2%*x+25%*y=30%*2050
33,2%*x+25%*y=615
33,2%*(2050-y)+25%*y=615
33,2%*2050-33,2%*y+25%*y=615 /*100
33,2*2050-33,2*y+25*y=61500
68060-8,2y=61500
-8,2y=61500-68060
-8,2y=-6560 /:(-8,2)
y=800 zł, x=2050-800=1250 zł.
  • Użytkownik Zadane
2009-10-14T17:52:47+02:00
30%*2050=3/10*2050=3*205=615

33,2%=0,332
25%=0,25

{x+y=2050 [/*(-1)]
{0,332x+0,25y=615 [/*4]

{-x-y=-2050
+{1,328x+y=2460
0,328x=410 [/:0,328]
x=1250

1250+y=2050
y=2050-1250
y=800

{x=1250
{y=800

Odp. Przedmioty te kosztowały 1250zł i 800zł.

:)